DTI Profiles for Rapid Description of Cohorts at the Clinical-Research Interface - Lock, Christine; Kwok, Janell; Kumar, Sumeet; Ahmad-Annuar, Azlina; Narayanan, Vairavan; Ng, Adeline S. L.; Tan, Yi Jayne; Kandiah, Nagaendran; Tan, Eng-King; Czosnyka, Zofia; Czosnyka, Marek; Pickard, John D.; et al. (Frontiers in Medicine, 2019)
Normal pressure hydrocephalus (NPH) is syndrome comprising gait disturbance, cognitive decline and urinary incontinence that is an unique model of reversible brain injury but it presents as a challenging spectrum of disease cohorts. Diffusion Tensor Imaging (DTI), with its ability to interrogate structural white matter patterns at a microarchitectural level, is a potentially useful tool for the confirmation and characterization of disease cohorts at the clinical-research interface. However, obstacles to its widespread use involve the need for consistent DTI analysis and interpretation tools. We present the use of DTI profiles, a simplistic interpretation methodology of the morphology of diffusivity parameters. We examined 13 patients with complex NPH, with comorbidities including cardiovascular risk burden and overlay from neurodegenerative disease, undergoing extended CSF drainage, clinical assessments and multi-modal MR imaging. Following appropriate exclusions, we compared the morphology of DTI profiles in such complex NPH responders and non-responders to exemplar DTI profiles from a cohort of classic NPH patients (n=16) demonstrating responsiveness of white matter injury to ventriculoperitoneal shunting. The mean age of patients was 71.3 7.6 years (10 male, 2 female). Clinical, cognitive and DTI profiles were achieved in twelve patients. Four patients responded to CSF drainage and eight patients were non-responders. Distinct DTI characteristics were demonstrated for complex NPH responders vs. non-responders. We found that the morphology of DTI profiles for responders mimicked DTI patterns in predominantly shunt-responsive patients undergoing intervention for classic NPH. Our findings suggest that it is possible to use DTI profiles to provide a methodology for rapid description of differing cohorts of disease at the clinical-research interface and to facilitate comparison of DTI morphological patterns across international collaborator datasets.